DAMPAK DISTRIBUTED ENERGY RESOURCES TERHADAP PROFIL TEGANGAN DAN RUGI DAYA PENYULANG BANTUL 05 - Muhammad Yusuf Falah; Adib Muhammad Arrasyid; Afrida Nurul Ulfa; Rizal Zulfiqri Ahmad; Jimmy Trio Putra (JPTE FT UNY, 2021)
ABSTRACT:To realize Indonesia's commitment to cut greenhouse effect, it is important to use environmentally friendly vehicles. On August 12, 2019, the Presidential Regulation on the velocity of Battery-Based Electric Motor Vehicle Program for land vehicle as a sign of the seriousness of the government applying this vehicle. This research is specific in terms of the provision of Public Electric Vehicle Charging Station (SPKLU) in Bantul refinery area, Yogyakarta after the installation of Photovoltaic (PV) plant as Distributed Energy Resources (DER). This study used a simulation of the Open Distribution System Simulator (OpenDSS) software distribution network in analyzing the comparison of voltage profiles and power losses before and after spklu installation. By optimizing the placement of SPKLU using Flower Pollination Algorithm (FPA) method using Matlab software that results in spklu placement on bus 58 by 300 kW, bus 37 by 301 kW, and bus 36 by 300 kW. The voltage profile changed from 0.9695 p.u to 0.9688 p.u and power losses from 53.3 kW to 56.1 kW.ABSTRAK:Untuk mewujudkan tanggungjawab Indonesia dalam mengurangi efek rumah kaca maka harus menggunakan angkutan ramah lingkungan. Pada tanggal 12 Agustus 2019 telah disahkan Perpres Percepatan Program Kendaraan Bermotor Listrik Berbasis Baterai sebagai transportasi jalan merupakan tanda seriusnya pemerintah mengaplikasikan kendaraan ini. Penelitian ini spesifik pada hal penyediaan Stasiun Pengisian Kendaraan Listrik Umum (SPKLU) pada area penyulang Bantul, Yogyakarta setelah pemasangan pembangkit Photovoltaic (PV) sebagai Distributed Energy Resources (DER). Penelitian ini menggunakan simulasi jaringan distribusi software Open Distribution System Simulator (OpenDSS) untuk mempelajari perbandingan profil tegangan dan rugi daya sebelum dan sesudah pengaplikasian SPKLU. Dengan optimasi penempatan SPKLU menggunakan metode Flower Pollination Algorithm (FPA) menggunakan software Matlab yang menghasilkan penempatan SPKLU pada bus 58 sebesar 300 kW, bus 37 sebesar 301 kW, dan bus 36 sebesar 300 kW. Profil tegangan berubah dari 0,9695 p.u menjadi 0,9688 p.u dan rugi-rugi daya dari 53,3 kW menjadi 56,1 kW.